2011
DOI: 10.2298/hemind110627056k
|View full text |Cite
|
Sign up to set email alerts
|

In vitro examination of oral tissue conditioners potential toxicity

Abstract: The oral tissue conditioners are applied temporarily to the gingival surface of a denture for the purpose of reconditioning the abused denture supporting tissues, allowing them to return to a normal, healthy state. According to chemical composition they can be classified into methacrylic and silicon conditioners. The objective of this research was to examine the potential toxicity of one, seven and thirty day extracts of different concentrations. Different effective concentrations (5, 12.5, 25 and 50%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 24 publications
3
14
0
3
Order By: Relevance
“…Cold polymerized acrylates induced the most intensive granulomatous reaction after both implantation procedures, which is in accordance with the results of examination of their cytotoxic effect [25][26][27] . The results of this study are in positive correlation with the findings of in vitro studies that proved stronger cytotoxic effect of soft and hard cold polymerized acrylates as compared to hot polymerized acrylates [28][29][30][31] .…”
Section: Fig 6 -A Two-week Implantation Period Of Triplex Hot Samplesupporting
confidence: 88%
“…Cold polymerized acrylates induced the most intensive granulomatous reaction after both implantation procedures, which is in accordance with the results of examination of their cytotoxic effect [25][26][27] . The results of this study are in positive correlation with the findings of in vitro studies that proved stronger cytotoxic effect of soft and hard cold polymerized acrylates as compared to hot polymerized acrylates [28][29][30][31] .…”
Section: Fig 6 -A Two-week Implantation Period Of Triplex Hot Samplesupporting
confidence: 88%
“…Author's earlier studies have shown possibilities for decreasing the amount of residual monomer and other potentially toxic substances in acrylic material samples by additional polymerization and immersion in a water bath [20,50]. Kostic et al investigated the effects of residual monomer reduction by immersion in a water bath on pressure yields stress and superficial structure of acrylic materials [26].…”
Section: Resultsmentioning
confidence: 99%
“…Komponente koje ulaze u sastav mekih akrilata u literaturi mogu biti toksične za oralna tkiva ukoliko se u potpunosti ne neutralizuju u procesu polimerizacije [8][9][10][11] . Kako ne postoji apsolutno vezivanje materijala u toku njegove pripreme i izrade zubnih proteza, u istraživanju se krenulo od pretpostavke da će u vremenu korišćenja mekih akrilata kao lajnera doći i do oslobađanja komponenti u okolni tečni medijum.…”
Section: Introductionunclassified